Electrochemical Metallization with Ni(II) from 5,10,15,20- Tetraquis(p-hydroxiphenyl)porfirin - Aguilera, E. N.; Blanco Jerez, Leonor María; Huerta, A. M.; Obregón, L. A. (2009)
The electro-synthesis of a nickel metalloporphyrin by using the 5,10,15,20-tetraquis(phydroxyphenyl)porphyrin (TPPOH) as binding agent is reported. Before the electrosynthesis, cyclic voltammetry technique was applied to establish the best conditions for the electrochemical reduction of the porphyrin to the di-anion radical. The electrosynthesis of the metalloporphyrin was done under the conditions found from voltammetry. The electrolysis was performed in a non-divided cell, with a nickel sacrificial anode and at controlled potential, in order to favouring the chemical formation of the metal-complex by reaction between the porphyrin dianion radical and Ni(II) ions, both of them electro-generated during the process. The effect of the use of an ultrasonic wave of 20 kHz in the metalloporphyrin electro-synthesis process was studied. The porphyrin, of free base, and the products obtained in both the absence and the presence of ultrasonic were characterized through Atomic Absorption, UV-Visible, IR and elemental analysis. The results of this characterization make available to establish that the process leads to the formation of the metalloporphyrin of Ni(II) with TPPOH, with an electrolytic efficiency greater than 80%. The application of the 20 kHz ultrasonic wave at the amplitude of the study favoured the yield of the reaction and did not lead to changes in the electrochemical mechanism.